THE BRAINSTORMING STRATEGY AND ITS IMPACT ON THE DEVELOPMENT OF STUDENTS' HIGHER-ORDER THINKING SKILLS FROM THE TEACHERS' POINT OF VIEW (American Journal of Research in Humanities and Social Sciences, 2024)
This study aimed to identify the impact of the brainstorming strategy on developing higher-order thinking skills (analysis, synthesis, evaluation) in light of some demographic and functional variables for teachers, by following the descriptive and analytical approach, and distributing the questionnaire tool to a random sample of (106) individuals. The study reached a set of results, the most important of which are: the presence of statistically significant differences in estimating the effect of the brainstorming strategy in developing higher-order thinking skills (analysis, synthesis, evaluation) among students from the teachers’ point of view due to the gender variable, as these differences were in favor of the analysis and synthesis skills. . There are statistically significant differences in estimating the effect of the brainstorming strategy in developing higher-order thinking skills (analysis, synthesis, evaluation) among students from the teachers’ point of view, attributed to the scientific specialization variable (educational subject), in favor of the synthesis skill. There are statistically significant differences in estimating the effect of the brainstorming strategy in developing higher-order thinking skills (analysis, synthesis, evaluation) among students from the point of view of teachers, attributed to the educational stage variable in favor of the evaluation skill. The study also found that there were statistically significant differences in estimating the effect of the brainstorming strategy in developing higher-order thinking skills (analysis, synthesis, evaluation) among students from the teachers’ point of view, attributed to the scientific specialization variable (educational subject), in favor of the evaluation skill. The study recommended the need to develop teaching programs aimed at developing higher-order thinking skills using other educational strategies and activities (classroom and non-classroom), and linking this in a practical way to homework and assignments